2023
DOI: 10.3389/fpsyg.2023.1074649
|View full text |Cite
|
Sign up to set email alerts
|

Leisure and meaning in life

Abstract: How people engage in leisure is an important but frequently underappreciated aspect of meaning in life. Leisure activities range from highly engaging and meaningful to subjectively trivial. Leisure itself is largely defined by meaning: The essence of leisure lies less in the specific activity than in the subjective perception of freedom, choice, and intrinsic motivation. People desire their lives to be meaningful, and leisure activities offer varying degrees of satisfying the basic needs for meaning (here cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 83 publications
0
1
0
Order By: Relevance
“…Several countries have implemented nationwide lockdowns to prevent the virus's transmission, severely restricting people's typical behaviors (e.g., van Bavel et al, 2020). The imposition of social distancing measures, including lockdowns and other infection prevention strategies, has restricted behavior and has been detrimental to people's psychological health and has increased stress, anxiety, and depression (e.g., Khan et al, 2020;Mascherini et al, 2021), potentially leading to a decline in people's psychological and subjective well-being (e.g., Kuykendall et al, 2018;Iso-Ahola and Baumeister, 2023). However, several studies have suggested that the Pandemic or lockdowns did not significantly affect well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Several countries have implemented nationwide lockdowns to prevent the virus's transmission, severely restricting people's typical behaviors (e.g., van Bavel et al, 2020). The imposition of social distancing measures, including lockdowns and other infection prevention strategies, has restricted behavior and has been detrimental to people's psychological health and has increased stress, anxiety, and depression (e.g., Khan et al, 2020;Mascherini et al, 2021), potentially leading to a decline in people's psychological and subjective well-being (e.g., Kuykendall et al, 2018;Iso-Ahola and Baumeister, 2023). However, several studies have suggested that the Pandemic or lockdowns did not significantly affect well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Leisure activities are pivotal in enhancing overall well-being ( Newman et al, 2014 ; for a review, see Iso-Ahola and Baumeister, 2023 ). However, the onset of the COVID-19 pandemic has substantially curtailed these activities.…”
Section: Introductionmentioning
confidence: 99%